RESTRUCTURING OF TITANIUM-POLYMER COMPOSITE UNDER IRRADIATION PROTON - Komarov, F.F.; Kupchishin, A.I.; Aryutkin, K.N. (Recent Contributions to Physics, 2018)
Investigations of the structure of samples of a composite material based on titanium and polymer. The simulation of processes occurring in the material under the influence of radiation.